Neuropsychiatric Aspects of Long Covid - Bintang Arroyantri Prananjaya; Muhammad Yusuf Wijahaska; Chris Alberto Amin; Carissa Delania; Ziske Maritska; Nita Parisa; Mohammad Hilal Atthariq Ramadhan (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Long COVID is a term used for persistent symptoms after being infected with COVID-19 with an estimated point of onset ranging from 3-12 weeks after infection. The risk factors for the occurrence of Long COVID are influenced by age, gender, comorbidity, ethnicity, and the severity of the acute phase. It is known that central, peripheral, and psychological factors play an important role in chronic fatigue, which is one of the most common symptoms of Long COVID. The most common neuropsychiatric clinical manifestations in Long COVID are sleep disturbances, fatigue, depression, anxiety disorders, decreased cognitive function or decreased concentration, and post-traumatic stress disorder. Therapeutic management for Long COVID cases involves various aspects, such as physical rehabilitation, management of pre-existing co-morbidities, mental health support management, and social services.